Computational Modeling of Liquid Droplets Moving on Rough Surfaces. Issue 1 (29th November 2013) - Rasool, Raheel; Osman, Muhammad; A. Sauer, Roger
Abstract: We present a de‐coupled approach for computational modeling of liquid droplets moving on rough substrate surfaces. The computational model comprises solving the membrane deformation problem and the fluid flow problem in a segregated manner. The droplet shape is first computed by solving the Young‐Laplace equation where contact constraints, due to the droplet‐substrate contact, are applied through the penalty method [1]. The resulting configuration constitutes the domain for the fluid flow problem, where the bulk fluid behavior is modeled by the unsteady Stokes' flow model expressed in Arbitrary Lagrangian‐Eulerian (ALE) framework. The entire analysis is performed in the framework of Finite Element Method (FEM). Application of the approach to the case of a droplet moving on a rough surface is presented as an example. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)